Effectiveness of a Program Based on Differentiated Instruction for Teaching Islamic Jurisprudence in Developing Reflective Thinking Skills Among Second-Year Secondary Students in Sana’a Governorate - Al-Ashwal, Salim Mohsen Saleh; Al-Jalal, Muhammad Ahmed; Al-Afif, Hamid Farhan (Journal of Curriculum and Teaching Methodology, 2025)
The aim of this research is to investigate the effectiveness of the differentiated instruction in teaching Islamic jurisprudence in developing reflective thinking skills among second-year secondary students in Sana’a Governorate. The researcher employed both the descriptive method for construction and development and the quasi-experimental method, as they are suitable for the nature of the study. The tools used included a list of reflective thinking skills consisting of 25 indicators categorized under five basic skills, as well as a reflective thinking skills test consisting of 30 questions. The sample comprised 80 second-year secondary students from Sana’a Governorate, divided into two equal and equivalent groups: an experimental group and a control group. The experimental group studied using the proposed program based on the differentiated instruction strategy during the second semester of the 2023-2024 academic year, while the control group was taught using the traditional method. The research yielded several significant findings, the most important of which were: the development of a list of reflective thinking skills and the presence of statistically significant differences at a significance level of (0.000) between the mean scores of the experimental and control groups in the post-application of the reflective thinking skills test, favoring the experimental group that learned according to the differentiated instruction strategy. Consequently, the following recommendations were made: to benefit from the training program prepared in this research for teaching students in other grades and subjects, and to incorporate the differentiated instruction strategy into the strategies used in training Islamic education teachers in colleges of education, as well as to train them on how to use it effectively.